Air-Bone Gaps Contribute to Functional Hearing Preservation in Cochlear Implantation. Issue 9 (October 2016) - Mattingly, Jameson K.; Uhler, Kristin M.; Cass, Stephen P.
Abstract : Objective: To examine the incidence and effect of postoperative air-bone gaps in subjects who received cochlear implants for the purpose of hearing preservation. Study Design: Prospective, multicenter, nonrandomized, repeated measures within subject design. Setting: Ten tertiary care institutions. Patients: Fifty adults participating in a multicenter clinical trial of the Cochlear Nucleus Hybrid implant system. Intervention(s): Cochlear implantation with Hybrid L24 electrode. Audiometric testing including air and bone conductive thresholds and tympanometry preoperatively and at multiple time points postoperatively for 1 year. Main Outcome Measure(s): Average air-bone gaps (ABG) and percentage of patients with ABGs (≥15 dB HL) measured for each time point for 1 year postoperatively at 250, 500, and 1000 Hz. Correlation of tympanograms and ABGs. Results: The mean ABGs at 250, 500, and 1000 Hz increased postoperatively ( p  <0.05). The percentage of patients found to have an ABG (≥15 dB HL) also increased postoperatively ( p  <0.05). ABGs persisted and were present at 1 year in >60% of patients at 250 Hz, in >38% at 500 Hz, and in >50% at 1000 Hz in those with residual hearing. No significant relationships were found between abnormal tympanograms and ABG. Conclusion: The incidence of ABGs postoperatively is higher than previously expected and does not correlate to abnormalities on tympanometry. ABGs can adversely affect the fitting of postoperative residual hearing and associated functional benefit. Additionally, intraoperative strategies should be used to potentially reduce ABGs, and bone conduction thresholds should be measured postoperatively. Abstract : Supplemental Digital Content is available in the text